Effect of land use change on climate elasticity of water quality at multiple spatial scales. Issue 11 (11th November 2022) - Khan, Mehran; Khan, Sunaid; Ullah Khan, Afed; Noman, Muhammad; Usama, Muhammad; Ahmad Khan, Fayaz; Haleem, Kashif; Khan, Jehanzeb
Abstract: Investigating the influence of land use change on climate elasticity of water quality (CEWQ) at multiple spatial scales is very critical for sustainable water management policies. The current research work investigated land use change–water–climate nexus through the lens of 32 water quality monitoring sites located at major rivers of Pakistan. The novelty of the current research work is the assessment of the instability consequences of precipitation and temperature CEWQ indicators owing to land use dynamics (2001–2019) at both sub-watershed and buffer scales. Precipitation elasticity values are lower and spatially homogeneous in comparison with temperature elasticity. Majority CEWQ-land use correlation coefficients have not shown any temporal trend with land use change except a few CEWQ indicators, namely pH, CO3, F, Ca, SiO2, silt, and clay. Temperature CEWQ developed many linear models with land use in comparison with precipitation CEWQ. A small number of land use classes cause instability consequences at the buffer scale in comparison with the sub-watershed scale. Savanna, shrublands, and ice and snow decline instability consequences of CEWQ indicators at both spatial scales. The identified land use classes that bring stability in CEWQ indicators are recommended to be incorporated in watershed management policies to bring sustainability in the aquatic environment. HIGHLIGHTS: Elasticity technique was used to gauge the response of water quality parameters to climatic factors. Water–land–climate nexus was developed to highlight interconnections among water, land, and climate. CEWQ showed instability consequences owing land use change at the buffer and sub-watershed scales. Precipitation CEWQ is homogenous in space. Sediments' responses to climatic drivers are compact and lower. Graphical Abstract